Dot extrusion bioprinting of spatially controlled heterogenous tumor models. (November 2022) - Wei, Xiaoyun; Huang, Beisi; Chen, Keke; Fan, Zicheng; Wang, Ling; Xu, Mingen
Graphical abstract: Highlights: A novel dot-extrusion printing system for one-step generation of GelMa hydrogel beads is established. Cell-laden GelMa hydrogel beads are flexibly and controllably deposited into heterogeneous 3D constructs. Tumor-stroma models with different spatial structures are accurately built to explore the complex tumor invasion behavior. Abstract: Bioprinting of cell-laden hydrogel constructs providing three-dimensional (3D) spatial pattern capacity and suitable cellular microenvironment have become essential tools in the field of tissue engineering. For heterogeneous tissue development, the printing approaches permitting controllable deposition of multicellular components in a flexible manner are urgently needed. Here, a facile dot-extrusion printing (DEP) system for one-step generation of cell-laden gelatin methacrylate (GelMa) hydrogel beads (GHBs) is developed, which allows size-tunable GHBs programmable positioned into complex 3D constructs. The GelMa is in situ semi-gelled at the printhead, thus enabling one-step generation of GHBs onto the platform, as a result of improved printing simplicity, fidelity and flexibility. The size and spatial position of the GHBs are adjustable by programming G-code parameters. Further, by integrating multiple printheads, GHBs encapsulating different cellular components can be printed to fabricate heterogeneous tissue constructs, and maintain the post-printed cell viability over 95%. As an example of application, two different tumor-stroma spatial phases were developed through spatial regionally printing tumor cells and normal fibroblasts into juxtapositional or overlapping microcapsule structures, giving an access to study the complex tumor-stroma interactions in different microenvironments. The developed DEP system thus holds promise for creation of complex and heterogeneous tissues toward various biology studies.